The predictive value of sFlt-1/PIGF ratio in high risk patients for the development of preeclampsia - Sunil, Isha; Sharma, Mitali (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: Hypertensive disorders of pregnancy constitute a major cause of maternal morbidity and mortality. Pre-eclampsia/eclampsia ranks second only to haemorrhage as a specific, direct cause of maternal mortality. A number of markers have been under study for the early detection of this disease. The study aims to evaluate the predictive value of sFlt-1/PlGF ratio for preeclampsia. Methods: This study was conducted in the Department of Gynaecology and Obstetrics of ASCOMS hospital, Jammu for a period of 6 months from Jan 2019 to June 2019. 50 antenatal patients attending the outpatient department with risk factors for developing preeclampsia were enrolled in the study. Their sFlT-1/PIGF ratio was determined at gestational age of 20 weeks to 37 weeks and its predictive value was evaluated. Results: In the present study, 8 patients developed preeclampsia subsequently. The mean sFlt-1/PIGF ratio values were significantly higher in the patients who developed preeclampsia (73.5) than who did not develop the disease (26.07). The positive predictive value at 1 week was 41.66% and negative predictive value was 100%. At 4 weeks, positive predictive value was 66.66% and negative predictive value was 100%. Conclusions: The present study suggests sFlt-1/PIGF ratio values are useful marker was a predictor of preeclampsia and values >38 were associated with preeclampsia. It is more useful in ruling out preeclampsia than ruling in the disease.